Neutrophil - Lymphocyte Ratio as a Reliable Predictor of Postoperative Outcome And Mortality In Delayed Cases Of Peripheral Arterial Embolism - Lefter Nasto; Tanyo Kavrakov; Hristo Abrashev (European Scientific Journal, ESJ, 2020)
Introduction: Peripheral arterial embolism (PAE) continues to pose a challenge to vascular surgeons and remains to be characterized by high morbidity, limb threat and mortality, often requiring urgent revascularization. Contemporary untreated arterial embolism is among the leading causes of morbidity and mortality within the vascular field. Detection of a fast and reliable biomarker for risk stratification and early post-treatment prognosis is important for those with PAE, so that individuals at high risk can be accurately treated and targeted for prevention.Complete blood count is inexpensive, comparatively routine, and is a practical laboratory test that gives important information about the patient’s formed blood contents. Routine peripheral blood counts may be useful in diagnosis and prognosis of many disorders, including peripheral vascular ischemic incidents. Neutrophil - lymphocyte ratio (NLR) has been shown to be an independent predictor of early and midterm amputation in patients with acute limb ischemia after revascularisation.Methods: Data was collected retrospectively from hospitalised patients, in the Vascular Surgery Clinic of University Hospital, Stara Zagora, Bulgaria, who had a diagnosis of PAE, from January 2010 to January 2019. Inclusion criteria were clinical data of an ischemic embolic incident of the limbs, untreated at least 12 hours from the onset of symptoms.Results: A single cutoff point was chosen to better inform clinical practice at a value of NLR 4.55, to maximize sensitivity andspecificity. The majority of patients from the group Who had a NLR under 4.55 had mild symptoms. Older patients however, were significantly more likely to have an elevated NLR. The incidence of diabetes and hypertension were not significantly higher in any group. There was a higher incidence of primary major amputations in the elevated NLR group. Of the 25 deaths during the course of the study, which were specifically attributed to cardiac causes, twelve (13.8%) occurred within the elevated NLR group and thirteen (8.7%) in the low NLR group.Conclusion: NLR is an easily accessible biomarker that conveys important information about the patient’s inflammatory activity and can be easily calculated from the differential WBC count, which is routinely performed on admission and is universally available.An elevated NLR could potentially be included in addition to the most common risk factors for mortality and poor post-treatment outcome including cardiac causes, age >70 years, history of stroke or previous MI, renal failure, and smoking history (at any time).